Biological control of Phytophthora root-rot of coorg mandarin (Citrus reticulata) by Trichoderma species grown on coffee waste - Sawant, Indu S; Sawant, S D; Nanaya, K A (The Indian Journal of Agricultural Sciences, 2012)
A study was conducted during 1989-1992 to find out the potential of biological control of root-rot of Â coorg mandarin (Citrusreticulata Blanco) caused by Phytophthora nicotianae Breda de Haan var parasitica (Dastur) Waterhouse and P. colocasiaeRacib. Trichoderma harzianum Rifai, Â virde Pers. ex S F Gray and Gliocladium virens Miller, Giddens & Foster, were foundwidely distributed in Citrus orchards, with population of 200-2000 colony-forming units/g soil. Seventeen isolates were foundhighly antagonistic to both Phyphthora spp under in-vitro condition. For large-scale multiplication of these fungi, localwaste (coffee-cherry husk, fruit skin and berry mucilage; poultry manure and mushroom-grown waste) was found suitable, giving20-30 million colony-forming units/g substrate. Pot trials amended with coffee-cherry husk and poultry manure in 1 : 2decreased feeder root-rot and increased the growth of coorg mandarin seedlings. It was on a par with best fungicidetreatments like Akomin 0.3%, metalaxyl + mancozeb (Ridomil MZ) (0.25%) spray, or drenching of chlorothalonil (0.2%). IsolatesE, T3, 3HR and D of T. harzianum and isolate B of T viride grown on cofee-cherry husk decreased the feeder root-rot andincreased the plant growth when applied @ 1 % inoculum in soil. Thus native Trichoderma spp can be multiplied on large scaleon easily available coffee waste and applied in the root zone of coorg mandarin plants either alone or with fungicide spraystor effective management of root-rot.